Cenozoic geoclimatic changes drove the evolutionary dynamics of floristic endemism on the Qinghai–Tibet Plateau - Guan-Long Cao; Xiao-Qian Li; Jun Zhang; Huan-Wen Peng; Hong-Lei Li; Andrey S. Erst; Florian Jabbour; Rosa del C. Ortiz; Pamela S. Soltis; Douglas E. Soltis; Wei Wang (Proceedings of the National Academy of Sciences, 2025)
The Qinghai–Tibet Plateau (QTP) harbors extraordinarily high levels of biodiversity and endemism. The region is warming at a rate twice the global average, yet the evolutionary dynamics of its unique biota are poorly understood. Here, we used the endemic land plant genera of the QTP to investigate how its floristic endemism was shaped over time by Cenozoic geoclimatic changes. We first clarified that the QTP hosts 82 endemic land plant genera; we found that the origins of these endemic genera were most likely driven by ecological niche and elevation differentiation, caused by the uplift of the QTP and associated climate change. By sampling 37 land plant clades that together encompass 1,740 species, covering all 82 endemic genera, we show that QTP floristic endemism had emerged by the Early Eocene. Furthermore, the unique biodiversity of the QTP comprises a mix of indigenous elements and immigrants. Among the three subregions of the QTP (Plateau Platform, Himalaya, and the Hengduan Mountains), the processes associated with floristic endemism are asynchronous, reflecting different geoclimatic events with the Miocene as a particularly critical period. The relative contributions of in situ speciation and immigration to the unique biodiversity of the three subregions are also markedly different; in situ speciation dominated in the Hengduan Mountains, which hosts the oldest endemic components of the flora and has served as an important “pump” and “sink” of unique biodiversity. These findings provide insights into how past geoclimatic events may have shaped floristic endemism on the QTP and also have important conservation implications.